Maximiliano de Wied-Neuwied e os indígenas do Brasil - Silva, Igor de Lima e (2011)
In this thesis we analyze how the Brazilian Indians, of the beginning of nineteenth century, are portrayed in the iconographic collection bequeathed by the German naturalist Maximilian of Wied-Neuwied. During the two years that he remained in Brazil, between 1815 and 1817, the traveler kept contact with different ethnic groups, especially Pataxó, Puri, Kamakã and Botocudo, and from these relations made a detailed description of their habits and customs. After the conclusion of his trip Wied-Newied published the work Reise nach Brasilien [Travels in Brazil, in the years 1815, 1816, 1817], which brought, in the form of verbal and visual text, data about Brazil. Using the collection of the traveler, we sought to demonstrate how the indigenous peoples of were portrayed by Wied-Neuwied, to do this, we interpret the engravings published in different editions and translations of his travel book, noting the interventions that the engravers made, changing the original context of the images.